2020
DOI: 10.1038/s41467-020-17160-1
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor freezing reflects tactile temporal expectation and aids tactile perception

Abstract: The oculomotor system keeps the eyes steady in expectation of visual events. Here, recording microsaccades while people performed a tactile, frequency discrimination task enabled us to test whether the oculomotor system shows an analogous preparatory response for unrelated tactile events. We manipulated the temporal predictability of tactile targets using tactile cues, which preceded the target by either constant (high predictability) or variable (low predictability) time intervals. We find that microsaccades … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 80 publications
(119 reference statements)
11
58
0
Order By: Relevance
“…These results suggest that oculomotor activity was adjusted to reach a minimum at the onset of the anticipated auditory target. These findings, consistent with our results in the visual 3 and tactile 13 domains, reveal that the execution of oculomotor events is modulated by target’s predictability, even when the target is auditory.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that oculomotor activity was adjusted to reach a minimum at the onset of the anticipated auditory target. These findings, consistent with our results in the visual 3 and tactile 13 domains, reveal that the execution of oculomotor events is modulated by target’s predictability, even when the target is auditory.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, as in the previous studies, that used a similar procedure but required an immediate motor response to the target (Amit et al, 2019;Tal-Perry & Yuval-Greenberg, 2020), we found stronger inhibition for fixed relative to varied conditions. The result suggests that pre-stimulus oculomotor inhibition occurs regardless of whether a response to the stimulus is required, and is consistent with previous evidence showing no correlation between the oculomotor inhibition effect and reaction time (Abeles et al, 2020;Amit et al, 2019;Dankner et al, 2017, but see Badde et al, 2020 for a different result). This finding provides additional support for the hypothesis that this marker reflects a general temporal expectation process to an upcoming event, regardless of whether responses were planned or not, making it a useful marker for studying temporal expectation irrespective of its motor consequence.…”
Section: Discussionsupporting
confidence: 91%
“…In line with these studies, in the present finding we observe no effect of saccadic events on behavioral outcome for both the duration and the tilt tasks. However, in a recent study, using a tactile discrimination task, such a benefit was found, as oculomotor inhibition prior to target onset was associated with enhanced tactile perception (Badde et al, 2020). Thus, it is possible that the oculomotor inhibition is advantageous for perception under specific circumstances, but at this stage, it is unknown what are the factors that determine this relation, and consequently whether the oculomotor inhibition effect has a functional role in the perception of an anticipated target.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations